EXPERIMENTAL STUDY OF ANORTHITE DISSOLUTION AND THE RELATIVE MECHANISM OF FELDSPAR HYDROLYSIS - Oelkers E.H.; Schott J. (My University, 1995)
Steady-state dissolution rates of anorthite (An96) were measured as a function of aqueous Si, Al, and Ca concentration at temperatures from 45 to 95°C and over the pH range 2.4 to 3.2 using a Ti mixed-flow reactor. All dissolution experiments exhibited stoichiometric dissolution. The concentration of aqueous Si, Al, and Ca ranged from #7 x 10-5 to #1 x 10-3 molal, #6 x 10-5 to #3.4 x 10-3 molal, and #5 x 10-5 to #0.1 molal, respectively, corresponding to calculated anorthite chemical affinities ranging from #115 to #65 kJ/mol. Measured anorthite dissolution rates at constant temperature are proportional to a1.5H+, where aH+ designates the activity of the hydrogen ion, and consistent with an apparent activation energy of 18.4 kJ/mol. Anorthite dissolution rates are independent of aqueous Al concentration, which is in contrast with the alkali feldspars, whose constant pH, far from equilibrium rates are proportional to a-0.33Al+3 (Oelkers et al., 1994; Gautier et al., 1994; E. H. Oelkers and J. Schott, unpubl. data). This difference suggests a distinctly different dissolution mechanism. For the case of both types of feldspars it appears that Al is more readily removed than Si from the aluminosilicate framework. Because it has a Si/Al ratio of 3, the removal of Al from the alkali feldspar framework leaves partially linked Si tetrehedra. Removal of Si still requires the breaking of Si-O bonds, and thus the overall alkali feldspar dissolution rate is controlled by the decomposition of a silica-rich surface precursor. The variation of alkali feldspar dissolution rates with aqueous Al activity stems from the fact that the formation of this precursor requires the removal of Al. In contrast, because it has a Si/Al ratio of 1, the removal of Al from the anorthite framework leaves completely detached Si tetrehedra. As a result, the removal of Si does not require the breaking of Si-O bonds, the rate controlling precursor complex is not formed by the removal of Al, and the overall dissolution rate is independent of aqueous Al concentration at far from equilibrium conditions. It can be inferred from these results that the variation of far from equilibrium aluminosilicate dissolution rates on aqueous Al depends on the number and relative strength of different bond types that need to be broken for mineral hydrolysis.